Podcasts for the Delivery of Medical Education and Remote Learning - Julliana Newman; Andrew Liew; Jon Bowles; Kelly Soady; Steven Inglis (JMIR Publications, 2021)
Podcasts are increasingly being recognized as an effective platform to facilitate the continuous professional development (CPD) of health care professionals (HCPs). Compared with face-to-face meetings and other more traditional forms of CPD, podcasts allow for flexible learning and are less expensive to develop. Podcasts are at the cutting edge of digital education and can be an important element of a pharmaceutical company's multichannel communications plan to improve HCP engagement and CPD in specific therapy areas. However, developing a successful podcast can have significant challenges. In this viewpoint paper, we provide our perspectives on medical podcasts as a medium for educating HCPs in the digital age. We describe our experience in developing an HIV-focused podcast for Australian HCPs, creating a series that has now expanded to other therapy areas in several countries. Practical considerations and unique challenges associated with industry-sponsored podcasts are outlined. Overall, we believe that the process of developing a podcast can be a challenging but rewarding experience, and CPD delivered via podcasting should be more routinely considered by pharmaceutical companies.